2004
DOI: 10.1167/iovs.03-0309
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Prevalence ofPITX2Microdeletions and Mutations in Axenfeld-Rieger Malformations

Abstract: Point mutations and gross deletions of PITX2 appear to produce an equivalent haploinsufficiency phenotype. Quantitative PCR is an efficient means of detecting causative PITX2 deletions in patients with AR and may increase the detection rate at this locus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 40 publications
2
59
0
Order By: Relevance
“…5 Broad phenotypic variability associated with FOXC1 and PITX2 variants has been reported before, 11,14,17,18 as it has in this study, although Shields 5 previously reported that the severity of ocular defects did not correlate with the development of glaucoma. FOXC1 and PITX2 both encode developmental transcription factors expressed in a tightly regulated temporal and spatial manner during development.…”
Section: Discussionsupporting
confidence: 55%
“…5 Broad phenotypic variability associated with FOXC1 and PITX2 variants has been reported before, 11,14,17,18 as it has in this study, although Shields 5 previously reported that the severity of ocular defects did not correlate with the development of glaucoma. FOXC1 and PITX2 both encode developmental transcription factors expressed in a tightly regulated temporal and spatial manner during development.…”
Section: Discussionsupporting
confidence: 55%
“…This finding provides further support for a potential role of PITX2 in SHORT syndrome and similar conditions. 18,29 Of particular note are three PITX2 mutations reported in our study. First, the deletion we identified involving the distant upstream region (but not the coding region) of PITX2 in one ARS patient is similar to our previously reported ARS case, 19 and thus our report highlights the importance of this recently discovered mechanism, loss of the upstream regulatory region, as a cause of ARS.…”
Section: Foxc1 Mutations: Phenotypes and Genotypesmentioning
confidence: 55%
“…The color reproduction of this figure is available at the European Journal of Human Genetics online. PITX2 and FOXC1 mutations in ocular syndromes LM Reis et al PITX2: 4.7% 18 and 16% 10 of ASD (neither study provided the proportion of ARS specifically). The variation is most likely due to differences in sample composition as our cohort is enriched with ARS cases with additional systemic defects, particularly dental and umbilical anomalies that appear to be strongly associated with PITX2 mutations.…”
Section: Foxc1 Mutations: Phenotypes and Genotypesmentioning
confidence: 95%
See 1 more Smart Citation
“…Chromosomal deletions including the PITX2 and FOXC1 genes leading to haploinsufficiency have been documented as causes of ARS. 29,30 In addition, several studies have demonstrated that duplication of FOXC1 can equally cause an ARS phenotype. 31,32 Overexpression of Pitx2 in animal models also causes ARS type phenotypes.…”
Section: Expression Of Asd Genesmentioning
confidence: 99%